UN sustainable development goals, good governance, and corruption: The paradox of the world's poorest economies - Mombeuil, C.; Hemantha, P.D. (Wiley, 2020)
The first objective of this study is to demonstrate that the UN sustainable development goals (SDGs) remain beyond reach for the world's poorest economies by analyzing the trends in the worldwide governance indicators (WGIs), corruption perception index (CPI), the GDP per capita, and the human development index (HDI) using the case of 10 former European colonies (e.g., Burundi, Burkina Faso, Central African Republic, Guinea-Bissau, Haiti, Madagascar, Niger, Sierra Leone, Togo, and the Democratic Republic of Congo). Second, this study compares three-panel regression models (pooled OLS model, fixed-effects model, and random effects model) to examine the influence of the WGIs on CPI, GDP per capita, and HDI and then derive the most appropriate model. Based on the results of these two objectives, a theoretical framework is drawn to provide specific recommendations to overcome some of the challenges to sustainable development in the selected countries
Keywords: corruption perception index, developing countries, GDP per capita, human development index, panel regression models, UN sustainable development goals, worldwide governance indicators